Comparative analysis of results of traffic modelling in simulation environments - Ivanova, Yoana; Boneva, Yordanka (Yearbook Telecommunications, 2021)
In the paper are presented the possibilities of various simulation products for agent-based modelling of complex processes related to traffic management in urban environments. The theoretical framework contains a description of a basic algorithm for traffic management at an intersection in order to better understand the experimental part in which is explained which input parameters are key for conducting an effective simulation study for the needs of the urban transport infrastructure. The selection of simulation environments is based on specific characteristics after evaluation by a number of basic criteria. The scientific and applied contribution of the research is expressed in a comparative analysis of the generated simulation results in the relevant software products, through which the author aims to prove their reliability and applicability.